Optimization of spray drying process and storage stability of pitaya, Hylocereus polyrhizus (Weber) Britton & Rose pell powder. - Ee, Shu Chee (2011)
Pitaya peel (Hylocereus polyrhizus), which consists approximately 22% of the whole fruit weight, is discarded during juice processing. Physico-chemical properties of the discarded pitaya peel were determined in order to evaluate its potential for recovery of any value-added materials. The moisture content of the peel was approximately 92.7% and it was low in total soluble solids, protein, ash and fat content. Betacyanin pigment (150.46 ± 2.19 mg/100 g) and pectin (10.8%) were high in the peel. Glucose, maltose and fructose were detected in the peel but not sucrose and galactose. The peel also had very high insoluble and soluble dietary fibre which had exhibited a good ratio of insoluble dietary fibre to soluble dietary fibre (3.8: 1.0). Therefore, it would be an economic advantage to the food industry if pitaya peel could be reutilized instead of being discarded. In our study, pitaya peel was converted into spray dried powder since it was a good source of fibre, pectin and natural colorant. Optimization of the spray dried conditions was carried out using response surface methodology (RSM). A central composite design (CCD) was employed to study the effect of inlet air temperature (155-175 ˚C), outlet air temperature (75-85 ˚C) and maltodextrin DE10 concentration (8-22% w/w) on the pitaya peel powder. The powders were analyzed for betacyanin retention, color, moisture, water activity, hygroscopicity and solubility. Spray dried pitaya peel powders were pink in color, high in betacyanin pigment retention, low in moisture content and had a water activity of 0.233-0.380. The significant (p < 0.05) response surface models with high coefficients of determination values (R2 > 0.85), ranged from 0.896 to 0.979 were fitted for the experimental data, thus indicating a satisfactory adjustment of the reduced response models for predicting the characteristic of pitaya peel powder as a function of spray dryer conditions. The result also indicated that linear term of maltodextrin concentration was found to be the most significant (p < 0.05) variable influencing the powder characteristics. Outlet temperature had the least effect on the studies variables. The overall optimum region resulted in desirable pitaya peel powder was predicted at a combined level of inlet air temperature (165 ˚C), outlet air temperature (80 ˚C) and maltodextrin DE10 (15% w/w). No significant difference (p > 0.05) was found between the experimental values and predicted values for all responses indicated that the optimum region obtained was valid. The storage stability of packed spray-dried pitaya peel powder during accelerated storage (45 ± 2 °C, 14 weeks) and room temperature (28 ± 2 °C, 6 months) were studied. Aluminium laminated polyethylene (ALP), amber glass bottle (GL) and low density polyethylene (LDPE) were used as packaging materials. The betacyanin pigment retention, moisture content, water activity, solubility, hygroscopicity and the color of peel powder were evaluated throughout the storage period. Storage temperatures and the type of packaging materials significantly (p < 0.05) affected all the studied parameters. Degradation of betacyanin pigment in the powders followed the first order reaction kinetics. The half life of betacyanin in peel powder kept at both accelerated and room temperature storage were calculated to be [ALP (t1/2 = 93.65 weeks), GL (t1/2 = 87.72 weeks) and LDPE (t1/2 = 76.15 weeks)] and [ALP (t1/2 = 103.43 months), GL (t1/2 = 62.43 months) and LDPE (t1/2 = 38.29 months)], respectively. The results demonstrated that pigment retention of peel powder after storing at both 45 °C (86.96-89.61%) and room temperature (89.04-95.84%) was high and thus implied that the spray-dried pitaya peel powders maybe used as a commercial food colorant. ALP was the best packaging material for keeping spray-dried pitaya peel powders.